The Influence of Product Price and Exchange Rate toward Export Volume of Adidas T-Shirts (A Case Study at PT. Apparel One Indonesia 1) - Affan Naufal Syafida; Karnowahadi - Karnowahadi; Fatchun - Hasyim (Admisi dan Bisnis, 2019)
This study aims to explain the influence of both product price and exchange rate variables and each partial influence toward export volume of Adidas t-shirts. This study used explanatory study type with quantitative approach. The independent variables of this study are product price and exchange rate, while the dependent variable is export volume of Adidas t-shirts. The data used in this study is secondary data in the form of time series within the period of May 2016 to December 2018. This study used multiple linear regression analysis in IBM SPSS 23. The analysis results of this study showed that together, both variables of product price and exchange rate are influencing export volume of Adidas t-shirts. While partially, the variable of product price has a negative and significant influence toward export volume of Adidas t-shirts. The variable of exchange rate has a positive but insignificant influence toward export volume of Adidas t-shirts